2019
DOI: 10.1088/1742-6596/1232/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ectomycorrhizal Fungi and Trichoderma harzianum on the Clove (Syzygium aromaticum L.) Seedlings Performances

Abstract: This study aims to find out the interaction effect of application combination of ectomycorrhizal fungi and Tc-Jjr-02 Trichoderma harzianum isolate on initial growth of clove seed (Syzygium aromaticum L.). The experiment was arranged factorially by using Completely Randomized Design; first factor: application of ectomycorrhizal fungi (without and with ectomycorrhiza), while the second factor: the application of Trichoderma fungi (without and with T. harzianum), the experiment was repeated 4 times. The variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Supported by previous research (Sutarman et al, 2019) that testing the ability of Rhizoctonia as a biofertilizer agent is usually close to its role as a biocontrol agent which explains the interrelationship between the suppression effect of pathogens and the effect of promoting plant growth and the emergence of plant resistance to pathogen attack.…”
Section: Introductionmentioning
confidence: 99%
“…Supported by previous research (Sutarman et al, 2019) that testing the ability of Rhizoctonia as a biofertilizer agent is usually close to its role as a biocontrol agent which explains the interrelationship between the suppression effect of pathogens and the effect of promoting plant growth and the emergence of plant resistance to pathogen attack.…”
Section: Introductionmentioning
confidence: 99%
“…According to the study conducted by Giuseppe et al [56] on lettuce, tomato, and zucchini seedlings, co-inoculation with Trichoderma atroviride MUCL 45632 and Glomusintraradices BEG72 strains significantly improved the height, shoot dry weight, root dry weight, chlorophyll index (SPAD), and the trace element content of the seedlings compared to seedlings inoculated with Trichoderma atroviride MUCL 45632 or Glomusintraradices BEG72 alone. With clove (Syzygiumaromaticum L.) seedlings as the research object, Sutarman [57] observed that the height, ground diameter, leaf number, and root structure exhibited a significant improvement in the case of the seedlings coinoculated with Trichoderma harzianum Tc-Jjr-02 and Ectomycorrhizal fungi. In addition, a significant difference was observed when comparing the co-inoculated seedlings with the seedlings that were inoculated with Trichoderma or Ectomycorrhizal fungi alone.…”
Section: Discussionmentioning
confidence: 99%
“…sebagai penyangga bagi cekaman lingkungan fisik dan kimia tanah terhadap benih. Sejalan dengan hasil percobaan ini, pada kecambah tanaman hortikultur seperti cengkeh, Trichoderma sp.juga mampu mendukung proses pertumbuhan kecambah [9].…”
Section: Pembahasanunclassified